A trade-off in stand size effects in the reproductive biology of a declining tropical conifer Callitris intratropica - Lawes, Michael J.; Taplin, Pascale; Bellairs, Sean M.; Franklin, Donald C. (Plant ecology, 2013)
Because wind pollination is inefficient over longer distances, plants dependent on it may suffer Allee effects (lower individual reproductive fitness with lower density). However, at higher density, individual reproductive fitness may suffer because of intraspecific competition. We investigate density-dependent effects, via stand size, on cone and seed production and seed germinability in a conifer endemic to tropical Australia. Callitris intratropica R.T. Baker & H.G. Smith is an obligate-seeding tree that often occurs in monodominant stands embedded within savannas and on the fringes of monsoon forests. We found that isolated trees (50—300 m from stands) were taller, of broader profile, and produced approximately twice the number of cones (∼407 cones per tree) as those in large stands (∼173 cones per tree), suggesting that monodominance generates intraspecific competition. The number of seeds per cone (27 seeds) was not related to stand size. However, a contrasting effect in which seed germinability was higher in large stands (∼20 vs. <10 % in small stands) was approximately compensatory and consistent with an Allee effect of wind pollination. The net effect of an approximately even trade-off between cone production and seed germinability was that there was neither an Allee or density-dependent effect of stand size on fitness, measured as the number of germinable seeds per tree. Nevertheless, because the likelihood of cross-fertilisation declines with distance, the ability of C. intratropica to persist as very isolated individuals may be limited.